A PRECIOUS HERB - GMELINA ARBOREA LINN. W.S.R TO ITS MEDICINAL USES AND PHARMACOLOGICAL ACTIVITY - Sangeeta, *Kumari; D.C, Singh; Safina, Khatoon (International Journal of Ayurveda and Pharma Research, 2017)
Traditional medicines play an important role in health services around the globe. About three quarter of the world population relies on plants and plant product for health care. Gmelina arborea Linn. an important medicinal plant is one of the most widely cultivated species of the family Verbenaceae. It is commonly known as Gambhari,  the term actually used by tribal people of Bihar. It is one of the herb mentioned in all ancient literature of Ayurveda in diseases like ulcer, diarrhoea, thirst, anaemia, leprosy, vaginal discharge, piles, fever and varieties of ailments. It is highly valued from the immemorial because of its vast medicinal properties. Gambhari is a fast growing deciduous tree occurring naturally throughout greater part of India at altitudes up to 1,500 meters. It is an essential component of Dashamula dravya (group of ten roots) and has been used for its valuable medicinal properties like Medhya (Intellect power), Keshya (Hair tonic) and Rasayana (Rejuvenator). Acharya Charaka mentioned Gambhari in Sothahara, Dahaprasamana, Virecanopaga mahakasaya and also explain its fruit as best among Rakta-Sangrahaka and Raktapittahara. The roots,  fruits and the leaves of Gambhari have great medicinal value therefore traditionally it was widely used as anthelmintic, antimicrobial, anti-diabetic, anti-aging, analgesic, diuretic, hepato-protective and antiepileptic agent. The present article provides all necessary information regarding its classical literature, general introduction, medicinal uses of its roots, leaves, flowers, fruit, bark, and pharmacological studies conducted till date.